2007
DOI: 10.18553/jmcp.2007.13.5.412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Physician Office Generic Drug Sampling System on Generic Dispensing Ratios and Drug Costs in a Large Managed Care Organization

Abstract: What is already known about this subject• Increasing the generic dispensing ratio (GDR) reduces direct drug costs for health plans and members.• Brand samples given to patients by physicians contribute to brand drug use.• There has been only 1 previously published study in the peerreviewed literature in which a generic drug sampling intervention had no discernable effect on GDR. What this study adds• This automated generic drug sampling system based in physician offices was associated with small increases in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Information about this managed care intervention and its effect on the overall (all drug) generic dispensing ratio (GDR) in this MCO was published previously. 26 The previous study found a 1.2-point higher GDR (55.3% vs. 54.1%) in the first year for prescribers participating in a generic drug sampling program (kiosk prescribers) compared with nonkiosk prescribers within the plan's physician network. In the second year, the GDR difference narrowed to 0.8 points, 59.9% versus 59.1%.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 93%
“…Information about this managed care intervention and its effect on the overall (all drug) generic dispensing ratio (GDR) in this MCO was published previously. 26 The previous study found a 1.2-point higher GDR (55.3% vs. 54.1%) in the first year for prescribers participating in a generic drug sampling program (kiosk prescribers) compared with nonkiosk prescribers within the plan's physician network. In the second year, the GDR difference narrowed to 0.8 points, 59.9% versus 59.1%.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 93%
“…Some of these tactics include (a) lower copayments for generics than for brands, (b) financial penalties for using a brand drug when a generic drug is available, and (c) step-therapy edits that require the use of a generic drug prior to initiating therapy with a branded product. At the physician level, Scott et al (2007) conducted a study at a health plan that assessed the impact of an office-based generic drug sampling system on GDR. 8 The health plan used an automated generic dispensing machine (kiosk) in physician offices to dispense 21 distinct generic drugs.…”
Section: Addition Of Generic Medication Vouchers To a Pharmacist Acadmentioning
confidence: 99%
“…At the physician level, Scott et al (2007) conducted a study at a health plan that assessed the impact of an office-based generic drug sampling system on GDR. 8 The health plan used an automated generic dispensing machine (kiosk) in physician offices to dispense 21 distinct generic drugs. In the first year of this program, the average overall GDR for physicians participating in the sampling program was 1.2 percentage points higher than for physicians who did not participate in the program.…”
Section: Addition Of Generic Medication Vouchers To a Pharmacist Acadmentioning
confidence: 99%
“…12 Recently, Conklin and colleagues acknowledge that many infections, including acute upper respiratory tract infections do not require initiation of any antibiotic therapy, and that the convenient presence of some type of promotion like "kiosks" could potentially have promoted the overuse of antibiotics for clinically inappropriate indications. [13][14][15] During the past 10 to 15 years, antibiotic-resistant organisms have increased steadily, and currently represent a threat to the treatment of illness, to the point where no antibiotics are available to treat some life-threatening infections. [16][17][18] An increase in research on infection control and interventions to improve patient safety can be expected during the coming 20 years.…”
Section: Introductionmentioning
confidence: 99%